2006
DOI: 10.1177/1082013206062234
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of Listeria Monocytogenes’ Growth Rate Under Different Temperatures and Acids

Abstract: A response surface model of Listeria monocytogenes' growth rate was built in this study under different temperatures (10°C, 15°C, 20°C, 25°C and 30°C) and acid concentrations: citric acid (0-0.4%) and ascorbic acid (0-0.4%); two ingredients which are often used in the food industry as preservatives. Mathematical validation was performed with additional samples at different conditions within the range of the model, obtaining acceptable values of root mean square error (0.0466), standard error of prediction (18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
2
46
0
1
Order By: Relevance
“…Among secondary models, RSM has been commonly used in predictive microbiology to describe the effects of environmental dependences on the growth parameters of microorganisms. Similar to previous reports, RSM have been shown to successfully as a function of factors, such as pH, NaCl, temperature, and other preservatives (Buchanan & Phillips, 1993;McClure et al, 1997;Wijtzes, Rombouts, Kant-Muermans, Van't Riet, & Zwietering, 1993) for the growth of Clostridium sporogenes (Dong, Tu, Guo, Li, & Zhao, 2007) and Leuconostoc mesenteroides (Zurera-Cosano, García-Gimeno, Rodríguez-Pérez, & Hervás-Martínez, 2006), death of Salmonella Enteritidis (Koutsoumanis, Lambropoulou, & Nychas, 1999), growth rate and lag time of Listeria monocytogenes (Augustin & Carlier, 2000;Carrasco et al, 2006) and inactivation of Listeria monocytogenes (Gao, Ju, & Jiang, 2006) under different experimental conditions.…”
Section: Introductionsupporting
confidence: 81%
“…Among secondary models, RSM has been commonly used in predictive microbiology to describe the effects of environmental dependences on the growth parameters of microorganisms. Similar to previous reports, RSM have been shown to successfully as a function of factors, such as pH, NaCl, temperature, and other preservatives (Buchanan & Phillips, 1993;McClure et al, 1997;Wijtzes, Rombouts, Kant-Muermans, Van't Riet, & Zwietering, 1993) for the growth of Clostridium sporogenes (Dong, Tu, Guo, Li, & Zhao, 2007) and Leuconostoc mesenteroides (Zurera-Cosano, García-Gimeno, Rodríguez-Pérez, & Hervás-Martínez, 2006), death of Salmonella Enteritidis (Koutsoumanis, Lambropoulou, & Nychas, 1999), growth rate and lag time of Listeria monocytogenes (Augustin & Carlier, 2000;Carrasco et al, 2006) and inactivation of Listeria monocytogenes (Gao, Ju, & Jiang, 2006) under different experimental conditions.…”
Section: Introductionsupporting
confidence: 81%
“…Ross, Dalgaard, and Tienungoon (2000) reported that predictive models should ideally have an AF = 1.00, indicating a perfect model fit where the predicted and actual response values are equal. However, Ross et al (2000) and Carrasco et al (2006) reported that the AF of a fitted model increases by 0.10-0.15 units for each predictive variable in the model. F model, as in this study, that forecasts a response from two predictive variables (temperature, time) may be expected to have AF values ranging from 1.20 to 1.30 (Ross et al, 2000) or an equivalent percentage error range of 20-30%.…”
Section: Predictive Model Fitting and Validationmentioning
confidence: 98%
“…The Fisher F-test results (very low p-values) demonstrated the high significance of the model and convey that the predictive variables (temperature, holding time) can be used to reliably predict the response variable. This study also dealt with the validation of the developed model using a set of data obtained from additional test runs, exclusive of those performed in the elaboration of the model, as recommended by Ross (1996) and Carrasco et al, 2006. Therefore, separate randomly selected data sets of 60 and 90°C, with holding times from 2 to 60 min, were analysed to determine the accuracy of the predicted model.…”
Section: Predictive Model Fitting and Validationmentioning
confidence: 99%
“…The survival capability of L. monocytogenes observed in the previous conditions presumes a potential hazard to the consumer since the microorganism can grow even at refrigeration temperatures which coincides with the behavior of the pathogenic microorganism in different substrates, and is thus considered a risk microorganism that in turn can resist low pH levels (Beales, 2004;Carrasco et al, 2006;Castro et al, 2007;Chattopadhyay, 2008;Huang, 2008;Pal, Labuza, & Diez-Gonzalez, 2008a, 2008bLe Marc et al, 2002;Penteado & Leitão, 2004a;Phan-Than et al, 2000;Tienungoon et al, 2000;Walter, Kabuki, Esper, Sant'Ana, & Kuaye, 2009). By contrast, a pH level of 4.0 in mamey pulps (pulps 7, 8, and 9) showed a hurdle on L. monocytogenes cells, since growth was restrained during the whole storage period (15 days) at both temperatures ( Fig.…”
Section: Response Of L Monocytogenes In Mamey Pulpsmentioning
confidence: 99%